Uji Cepat Toleransi Tanaman Padi terhadap Cekaman Rendaman pada Fase Vegetatif - ,, Yullianida; Ardie, Sintho Wahyuning; Aswidinnoor, Hajrial (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTThe major constraint of rice cultivation in the flood-prone area is the lack of tolerant varieties. A rapid screening method have to be developed under controlled environments, such as a green house, to improve the effectiveness and efficiency of the selection under submergence condition. The aim of this research was to study the correlation beetween selection methods in greenhouse and in the field. This experiment was conducted at a green house of Muara Experimental Station, Bogor in 2011/2012. The experimental designs used were randomized complete design for greenhouse experiment and randomized complete block design for field experiment, with three replicates respectively. There were four sub-experiments in the greenhouse experiment, grouped based on seedling age (10 days and 35 days after seeding) and duration of submergence (10 days and 14 days). Those sub-experiments in the green house were compared with the experiment in the field. The results showed that there was strong correlation between recovery percentage in the green house and percentage recovery in the field. The same correlation indeed happen between recovery percentage in the green house to grain yield. Complete submergence at 10-day-old seedlings in green house could be developed as rapid selection method for submergence tolerant rice.Keywords: aciotic stress, correlation, flooding, Oryza sativa